Small marker chromosomes in man: origin from pericentric heterochromatin of chromosomes 1, 9, and 16. Issue 3 (March 1990) - Callen, D F; Ringenbergs, M L; Fowler, J C; Freemantle, C J; Haan, E A
Abstract : Three patients with different marker chromosomes were screened by in situ hybridisation using biotinylated probes to chromosome specific pericentric repeats to determine the chromosomal origin of the marker. Each marker had a different origin, with one from each of chromosomes 1, 9, and 16. This is the first time that autosomal marker chromosomes consisting of a small ring have been shown to be derived from the pericentric heterochromatin of metacentric and submetacentric chromosomes. Evidence suggests that such markers are not associated with any significant risk of phenotypic abnormalities, but additional cases need to be studied.